Representation and Identity Construction of Ethnic Minorities from Discourses in Government Media (Shiksha Shastra Saurabh, 2018)
Discourse is the common sense language that represents the society, culture, social groups, group behaviours, socio-cultural identities and political ideologies. It signifies communication as a whole. Media gives space for people’s voices in its programs and publications. In the same way, media is a common representative of the voices of all the ethnic communities regardless of majority or minority in its true principle. However, the languages and voices of all ethnic communities have not been represented in the discourse of government media in Nepal. In such a situation, this research aimed to; examine the representation of ethnic-minority languages in the discourses of government media of Nepal; critically assess the socio-cultural and political cognitions of the ethnic-minorities throughout the discourses in those media, and; identify the various identities constructed by the speakers of ethnic-minority languages through the discourses in government media. The finding of the study shows that our of 125 languages spoken in Nepal only 22 ethnic languages are represented in the discourse of Nepalese government media and the ethnic minority felt themselves being included within the national discourse when they found their discourses being represented in public media.